The potential of agrobiodiversity for improving diets and nutrition in Ghana - Vernooy, Ronnie (2021)
This report gives an overview of current use and conservation practices and related knowledge of neglected and under underutilized species in Ghana, a brief description of the roles of key stakeholders (government, knowledge institutes, private sector and civil society), identification of knowledge gaps, and a strategy for the promotion of NUS.